Defining service quality for tramp shipping - Tay, Wei Jun. (2011)
Tramp shipping constitutes a prominent segment of the shipping market. It accounts for 56% of the world seaborne trade (2006) and the fleet of bulk carriers and oil tankers represent 73.1% of the world fleet (2010). As customers increasingly seek value from service providers for low price but yet high quality services, there is a pressing need to define service quality for the tramp sector. However, no prior research has been conducted for this market segment. This study recognizes the gap in the existing maritime literatures. It aims to propose a service quality (SQ) model to address such a gap. The proposed SQ model would comprise of important attributes that defines a quality tramp shipping service, from the perspective of the shipper. This study focuses only on the dry bulk and liquid bulk trade within the tramp sector. In addition, this study will investigate if a perception gap exists between tramp shippers and tramp service providers;; dry bulk shippers (DBS) and liquid bulk shippers (LBS); big tramp shippers and small tramp shippers (SMEs); dry bulk shippers (DBS) and dry bulk service providers (DBSP); liquid bulk shippers (LBS) and liquid bulk service providers (LBSP).